2008
DOI: 10.1016/j.devcel.2007.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Keap1/Nrf2 Signaling Regulates Oxidative Stress Tolerance and Lifespan in Drosophila

Abstract: Keap1/Nrf2 signaling defends organisms against the detrimental effects of oxidative stress and has been suggested to abate its consequences, including aging-associated diseases like neurodegeneration, chronic inflammation, and cancer. Nrf2 is a prominent target for drug discovery, and Nrf2-activating agents are in clinical trials for cancer chemoprevention. However, aberrant activation of Nrf2 by keap1 somatic mutations may contribute to carcinogenesis and promote resistance to chemotherapy. To evaluate potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
682
4
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 612 publications
(717 citation statements)
references
References 47 publications
27
682
4
4
Order By: Relevance
“…Similarly, disruption of Nrf2 impairs the resolution of hyperoxia-induced acute lung injury and inflammation in mice (11). INrf2-Nrf2 signaling has also been shown to regulate oxidative stress tolerance and life span in Drosophila (12). Furthermore, Nrf2…”
mentioning
confidence: 99%
“…Similarly, disruption of Nrf2 impairs the resolution of hyperoxia-induced acute lung injury and inflammation in mice (11). INrf2-Nrf2 signaling has also been shown to regulate oxidative stress tolerance and life span in Drosophila (12). Furthermore, Nrf2…”
mentioning
confidence: 99%
“…Alternatively, there may be sex differences in the mechanisms that control the Keap1‐Nrf2 pathway. For example, Sykiotis & Bohmann (2008) reported that D . melanogaster carrying a loss of function mutation in Keap1 had increased Nrf2 activity, increased oxidative stress resistance, and elevated longevity, but in male flies only.…”
Section: Discussionmentioning
confidence: 99%
“…54,55 The activation of Nrf2 signaling by a Keap1 loss-of-function mutation augments tolerance to oxidative stress and confers increased lifespan in Drosophila. 55 Nrf2-dependent signaling has been reported to restore the loss of proteostasis and prevent premature aging in Drosophila.…”
Section: Nrf2 In Agingmentioning
confidence: 99%